Morbidity and mortality after robot‐assisted radical cystectomy with intracorporeal urinary diversion in octogenarians: results from the European Association of Urology Robotic Urology Section Scientific Working Group. (5th November 2020) - Mortezavi, Ashkan; Crippa, Alessio; Edeling, Sebastian; Pokupic, Sasa; Dell'Oglio, Paolo; Montorsi, Francesco; D'Hondt, Frederiek; Mottrie, Alexandre; Decaestecker, Karel; Wijburg, Carl J.; Collins, Justin; Kelly, John D.; et al.
Abstract : Objectives: To evaluate the postoperative complication and mortality rate following laparoscopic radical cystectomy (RARC) with intracorporeal urinary diversion (ICUD) in octogenarians. Patients and Methods: We conducted a retrospective analysis comparing postoperative complication and mortality rates depending on age in a consecutive series of 1890 patients who underwent RARC with ICUD for bladder cancer between 2004 and 2018 in 10 European centres. Outcomes of patients aged <80 years and those aged ≥80 years were compared with regard to postoperative complications (Clavien–Dindo grading) and mortality rate. Cancer‐specific mortality (CSM) and other‐cause mortality (OCM) after surgery were calculated using the non‐parametric Aalen‐Johansen estimator. Results: A total of 1726 patients aged <80 years and 164 aged ≥80 years were included in the analysis. The 30‐ and 90‐day rate for high‐grade (Clavien–Dindo grades III–V) complications were 15% and 21% for patients aged <80 years compared to 11% and 13% for patients aged ≥80 years ( P = 0.2 and P = 0.03), respectively. In a multivariable logistic regression analysis adjusting for pre‐ and postoperative variables, age ≥80 years was not an independent predictor of high‐grade complications (odds ratio 0.6, 95% confidence interval 0.3–1.1; P = 0.12). The non‐cancer‐related 90‐day mortality was 2.3% for patients aged ≥80 years and 1.8% for those aged <80 years, respectively ( P = 0.7). The estimated 12‐month CSM and OCM rates for those aged <80 years were 8% and 3%, and for those aged ≥80 years, 15% and 8%, respectively ( P = 0.009 and P < 0.001). Conclusions: The minimally invasive approach to RARC with ICUD for bladder cancer in well‐selected elderly patients (aged ≥80 years) achieved a tolerable high‐grade complication rate; the 90‐day postoperative mortality rate was driven by cancer progression and the non‐cancer‐related rate was equivalent to that of patients aged <80 years. However, an increased OCM rate in this elderly group after the first year should be taken into account. These results will support clinicians and patients when balancing cancer‐related vs treatment‐related risks and benefits.